Effects of overweight on luminal diameter, flow velocity and intima-media thickness of carotid arteries - Özdemir, Hüseyin; Artaş, Hakan; Serhatlio?lu, Selami; O?ur, Erkin (My University, 2006)
Purpose: To the best of our knowledge, there are only a few previous studies on the effects of overweight on extracranial carotid arteries. We aimed to investigate the effects of overweight on flow velocities, luminal diameters and intima media thicknesses (IMTs) of the common and internal carotid arteries (CCA, ICA). Materials and methods: A prospective study on color duplex sonography of the extracranial arteries was performed in 71 adults, ages between 25-58 years old. The body mass index (BMI) was found to be normal in 24 (group 1) and high in 47 (group 2) subjects of the study group. Flow velocity (FV), luminal diameter and IMT of carotid arteries of all the participants were measured. Results: There were significant differences between group 1 and group 2 in the following parameters; luminal diameters of the right CCAs were significantly larger in group 2, peak-systolic FV of ICAs were significantly lower in group 2 than in group 1 and ICA end-diastolic FVs were significantly lower in group 2 than in group 1. Conclusion: The present data shows that there is a correlation among carotid artery luminal diameter, FVs and overweight. In the overweight subjects, the increased luminal diameter and decreased FVs can point at the early stage of atherosclerosis. The influence of adiposity on atherosclerosis is very complex and varies with gender and age, therefore we need larger series and further investigation. © Turkish Society of Radiology 2006.
Keywords: Body mass index; Carotid arteries; Color Doppler; Ultrasonography